EFFECTIVE METHODS FOR LEARNING ENGLISH EASILY - Umarova Munavvar Nurmuhammedovna; Anorboyeva M. S (TADQIQOTLAR, 2025)
Abstract This  article  discusses  effective  and  simple  methods  for  learning  English.  It focuses  on  techniques  that  are  suitable  for  beginners  and  intermediate  learners, including interactive learning, technology integration, and daily practice routines.